2020
DOI: 10.1101/2020.08.30.274290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two-stage Dynamic Deregulation of Metabolism Improves Process Robustness & Scalability in EngineeredE. coli

Abstract: We report improved strain and bioprocess robustness as a result of the dynamic deregulation of central metabolism using two-stage dynamic control. Dynamic control is implemented using combinations of CRISPR interference and controlled proteolysis to reduce levels of central metabolic enzymes in the context of a standardized two-stage bioprocesses. Reducing the levels of key enzymes alters metabolite pools resulting in deregulation of the metabolic network. The deregulated network is more robust to environmenta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Importantly, this methodology enables predictability across scales from microtiter plates to instrumented reactors. 22,24 This enables reliable scale up of a strain or strain variant identified using the microfermentation protocol.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, this methodology enables predictability across scales from microtiter plates to instrumented reactors. 22,24 This enables reliable scale up of a strain or strain variant identified using the microfermentation protocol.…”
Section: Introductionmentioning
confidence: 99%
“…This is not to say that the autoinduction protocol cannot be leveraged in metabolic engineering programs, but we have recently demonstrated that for small molecules, performance of the 2-stage wash protocol in microtiter plates is predictive of performance in larger minimal media bioreactors, again a least for a subset of our engineered E. coli . 21,22…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lynch and colleagues combined phosphate limitation with a metabolic valve approach to limit cell growth and adjust its metabolism respectively. This led to the increased production of both small molecules 12 and proteins 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, microbial-based biosynthesis has been attempted to produce many value-added compounds from simple carbon sources [22][23][24][25][26][27], including GA and pyrogallol [28,29]. GA and pyrogallol biosynthetic pathways generally extended from 4-hydroxybenzoic acid (4-HBA), which was an Escherichia coli (E. coli) endogenous compound generated from the shikimate pathway [28].…”
Section: Introductionmentioning
confidence: 99%